2016
DOI: 10.12788/jcso.0215
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary breast and ovarian cancer: risk assessment in minority women and provider knowledge gaps

Abstract: Background The Georgia Breast Cancer Genomics Project identifed minority and underserved women at high risk for hereditary breast and ovarian cancer based on family history. Education, web-based screening, genetic counseling, and testing were provided in public health and primary care settings in accordance with evidence-based recommendations and guidelines. Objectives To assess risk of hereditary breast and ovarian cancer (HBOC) among minority and underserved women, provide genetic services according to evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…While EHR messaging of the ordering clinician was found to be the most effective method of referral for both scheduling (30.0%) and uptake (17.2%) of genetic counseling, these rates remain less than ideal. However, our uptake rate was not dissimilar from that reported in previous studies 3% to 50% [17][18][19][20][21][22][23][24][25]. While overall uptake was low, only 8% of screen-positive participants had previously received genetic counseling, suggesting a substantial increase in the identification of at-risk individuals.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…While EHR messaging of the ordering clinician was found to be the most effective method of referral for both scheduling (30.0%) and uptake (17.2%) of genetic counseling, these rates remain less than ideal. However, our uptake rate was not dissimilar from that reported in previous studies 3% to 50% [17][18][19][20][21][22][23][24][25]. While overall uptake was low, only 8% of screen-positive participants had previously received genetic counseling, suggesting a substantial increase in the identification of at-risk individuals.…”
Section: Discussioncontrasting
confidence: 64%
“…These studies vary by the method of identification and follow-up, setting (clinical, research, public health) and target population (affected or unaffected women). Identification of individuals at-risk for HBOC through various protocols has ranged from 2.7% to 13.9% and uptake of genetic counseling from 3% to 50% [17][18][19][20][21][22][23][24][25]. Application in a research setting, proband history of breast cancer, use of a patient navigator/direct contact, free access to genetic counseling and/or testing, and availability of telephone counseling have resulted in higher rates of uptake [16,21,22,25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, to date, uptake of HBOC screening has been uneven, with most programs identifying individuals in specialty care settings or relying on tumor registries, domains in which well-educated whites and those who already have cancer are overrepresented [44,45]. Efforts to implement HBOC screening in primary-care, community-based settings have found that poor women and women of color are less likely to be screened than their white and wealthier peers [46,47,48,49].…”
Section: Potential For Implementation Of Genomic Applications To Pmentioning
confidence: 99%